Barriers for the evaluation of advanced therapy medicines and their translation to clinical practice: Umbrella review. Issue 12 (December 2022) - Aguilera-Cobos, Lorena; Rosario-Lozano, María Piedad; Ponce-Polo, Angela; Blasco-Amaro, Juan Antonio; Epstein, David
Highlights: The specificities of ATMPs should be considered throughout their development process. Creation of mechanisms to facilitate the translation of ATMPs from research to clinical routine. Homogenisation of regulation and evaluation are key to the success of ATMPs. Reimbursement mechanisms must be adapted to enable patient access. Multidisciplinary groups and databases increase the likelihood of success of ATMPs. Abstract: Advanced therapy medicinal products (ATMPs) are a fast-growing field of medicine with wide potential application. Nevertheless, so far, only 19 have obtained European Union (EU) marketing authorisation and only 13 of these have translated successfully into clinical practice. This study conducts an umbrella review to identify the main barriers for the evaluation of ATMPs and their translation into clinical practice across the development lifecycle. 71 systematic reviews were included, of which 50 dealt primarily with effectiveness and safety, 13 with translation from pre-clinical to human subjects. Others dealt with economic issues and translation from health technology assessment to market access. The literature highlights the importance of synergistic research groups or networks that collaborate across the in-vitro science, preclinical and clinical investigation phases, and the role of private investor capital and public-private collaborations. Most ATMPs reviewed seem to have a favourable safety profile although considerable uncertainties remain. Randomised controlled trials are not always feasible in these patient groups. Greater sharing of data is recommended, both at preclinical and post-marketing real world evidence. There are considerable variations between EU countries in how they regulate hospital exemption for ATMPs, and this can lead to inequitable access for patients.